2008
DOI: 10.1007/s10979-007-9106-8
|View full text |Cite
|
Sign up to set email alerts
|

A third verdict option: Exploring the impact of the not proven verdict on mock juror decision making.

Abstract: In most adversarial systems, jurors in criminal cases consider the binary verdict alternatives of "Guilty" and "Not guilty." However, in some circumstances and jurisdictions, a third verdict option is available: Not Proven. The Not Proven verdict essentially reflects the view that the defendant is indeed culpable, but that the prosecution has not proven its case beyond a reasonable doubt. Like a Not Guilty verdict, the Not Proven verdict results in an acquittal. The main aim of the two studies reported here wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 33 publications
(38 reference statements)
3
62
0
Order By: Relevance
“…Confidence does not always equal accuracy, however (Hall et al, 2007) 18 . Hope et al 5 also found that the different verdict systems did not have a significant impact on the juror's perception of guilt surrounding the defendant.…”
Section: Review Of Empirical Studies Surrounding the Not Proven Verdictmentioning
confidence: 97%
See 1 more Smart Citation
“…Confidence does not always equal accuracy, however (Hall et al, 2007) 18 . Hope et al 5 also found that the different verdict systems did not have a significant impact on the juror's perception of guilt surrounding the defendant.…”
Section: Review Of Empirical Studies Surrounding the Not Proven Verdictmentioning
confidence: 97%
“…In addition, Hope et al 5 demonstrated that irrespective of verdict or evidence weight, verdicts made in the three-verdict system allowed the mock jurors to feel more confident that they had reached the correct verdict than their binary verdict system counterparts. Confidence does not always equal accuracy, however (Hall et al, 2007) 18 .…”
Section: Review Of Empirical Studies Surrounding the Not Proven Verdictmentioning
confidence: 99%
“…The dependent variable for the design considered in this section is a jury level variable so that everybody in the same jury has the same value. For example, it might be whether the jury said guilty or not guilty (though see Hope, Greene, Memon, Gavisk, & Houston, 2008, for allowing more options), or the proportion of guilty verdicts, or it might be of some other characteristic of the jury, like whether the jury discussed ‘forbidden topics’ (Greene, Hayman, & Motyl, 2008). Greene et al research on jury deliberation provides a good example of how to analyse data of this type (and a good example of combining qualitative and quantitative data).…”
Section: Modelling Jury Rather Than Juror Behaviourmentioning
confidence: 99%
“…Indeed, in the course of a trial, the main task that every judge has to face concerns the evaluation of various pieces of evidence from a variety of different sources, with the aim of integrating such information into a single decision of conviction or acquittal of a defendant. Presumably, a judge arrives at a certain subjective estimation of the likelihood that the defendant is guilty and decides whether such likelihood is greater or lesser than Houston, 2008;Shapiro, 1991;Wright & Hall, 2007). In such terms, an issue of considerable interest is the following: how do judges integrate various pieces of information in order to make their judgement?…”
Section: Introductionmentioning
confidence: 99%